The Relationship Between Diet and Stroke Severity in Adult Patients at RSUD X Bekasi - Muhammad Al-Amin R. Sapeni; Aisyah Latifa Amalia; Lastriyanti Lastriyanti; Toar Calvin Christo Paat (PT.Mantaya Idea Batara, 2024)
Currently, stroke attacks have shifted from infecting the elderly (elderly), to now being of productive age or adulthood (early and middle) which has an impact on disability and death. World Health Organization (2020), states that the incidence of stroke at a young age has increased in recent years. Meanwhile, based on Riskesdas data (2018) it states that the incidence of stroke in 2018 at the age of more than 15 years is 10.9% or the equivalent of 2,120,362. This can occur due to dietary factors which are known to have a negative impact on body health. This study aims to determine the relationship between diet and stroke severity in adult patients at RS X Bekasi. The type of research in this research is descriptive research with a quantitative approach and with a cross-sectional research design. Data collection was carried out using the Dietary Questionnaire and the National Institute of Health Stroke Scale (NIHSS) observation sheet for 30 respondents who were hospitalized at RS X Bekasi. Then, the data were analyzed using SPSS with the Chi-Square test. The results of this study indicate that there is no relationship between diet and stroke severity in adult patients at X Bekasi Hospital which is indicated by a significant value (p-value) of 0,185 (? > 0.05) and has a weak relationship indicated by a correlation coefficient value of r 0.134. Diet is not related to Stroke Severity Rate of Adult Patients at X Bekasi Hospital.